2014
DOI: 10.1017/s0950268814000806
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis A infection in patients with chronic viral liver disease: a cross-sectional study in Jahrom, Iran

Abstract: Infection with hepatitis A virus (HAV) in patient with chronic liver disease (CLD; due to hepatitis B or hepatitis C) may cause severe disease and fulminant liver failure. This study aimed to determine the seroprevalence of HAV antibodies in patients infected with HCV or HBV in Iran (Jahrom city). A total of 159 patients with underlying CLD were recruited between September 2012 and February 2013. Serum samples were collected from each patient and tested for anti-HAV using enzyme-linked immunosorbent assay (ELI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 29 publications
(45 reference statements)
1
13
1
Order By: Relevance
“…When anti-HAV IgG positivity was assessed in terms of sex, no difference was found in most of the studies as in our study 13 , 14 , 20 , 21 , but there are also study results showing that female sex is an independent risk factor 18 , 19 . More anti-HAV IgG seropositivity was found in female patients in the study carried out in Korea.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…When anti-HAV IgG positivity was assessed in terms of sex, no difference was found in most of the studies as in our study 13 , 14 , 20 , 21 , but there are also study results showing that female sex is an independent risk factor 18 , 19 . More anti-HAV IgG seropositivity was found in female patients in the study carried out in Korea.…”
Section: Discussioncontrasting
confidence: 50%
“…The anti-HAV IgG positivity was found to be statistically higher in our study in patients older than 40 years compared with those younger than 40 years of age. Although an age above 40 years was found to be a risk factor for anti-HAV IgG seropositivity in the Korean study 19 , the anti-HAV IgG seropositivity was found to be significantly higher in chronic hepatitis patients older than 30 years of age in a study carried out in Iran 18 . A study carried out by Saab et al 14 in the USA has shown that patients aged between 51 and 70 years have a higher risk of being exposed to HAV than patients younger than 51 years of age.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Hepatitis A virus (HAV), a member of the Picornaviridae family (1), is an epidemiological important virus with a worldwide distribution and high incidence in low-income countries (2). HAV can be transmitted via different pathways, such as fecal-oral route and contaminated food and water (3).…”
Section: Introductionmentioning
confidence: 99%
“…Decompensation of preexisting cirrhosis as well as increased morbidity and mortality has been reported for HEV1 superinfection among patients with chronic hepatitis C (5). Progression of chronic hepatitis to fulminant hepatitis and cirrhosis due to HCV H Sero-Epidemiology of Hepatitis E in HCV patients infection may be caused by HEV coinfections or other hepatitis agents (6,7). Severe response of the immune system to hepatitis viruses and direct cytopathic effect of HEV can cause liver fibrosis progression and cirrhosis (8).…”
Section: Introductionmentioning
confidence: 99%